The Influence of Leadership And Work Motivation on The Performance of 4 Star Hotel Employees in North Bandung (Case Study in Rooms Division Department) - Siahaan, Rudy Parlindungan; Danurdara , Ananta Budhi; Karsuki, Lucky; Wanti, Wanti Arum; Choirudin, Nor Ismawanto; Binti Hassan, Hafizah (Politeknik Pariwisata Makassar, Indonesia, 2025)
The objective of this study was to obtain empirical evidence about the influence of leadership and motivation on the performance of employees of a four-star hotel in the Rooms Division Department in the north of Bandung. The findings are expected to help the company and practitioners develop human resources management. The study was conducted at Hotel X, Hotel Y, dan Hotel Z. It used a quantitative research approach with a survey method, and the type of research was Descriptive Research and Explanatory Research, with a time horizon in the form of cross-sectional data that shows a picture of a situation at a specific time. The study's hypothesis was tested with the statistical method of path analysis. Path analysis is a statistical tool used to test the study's hypothesis. According to research test results, there is a considerable correlation between employee performance and leadership and motivation, either fully or partially.